We are still here: Re-centering the quintessential subject of intersectionality - Chantler, Khatidja; Thiara, Ravi K. (Atlantis, 2017)
This paper argues that “Black woman” should remain the quintessential subject of intersectionality as we are concerned that racialization has been submerged within intersectionality debates. Drawing on research and policy related to violence against women in minoritized communities in the UK, we (re)interrogate the explanatory power and effects of intersectionality.